An investigation of the effects of humic acid on soil erosion and loss of phosphorus from soil to runoff: Experiment and modeling - Chen, Minghong; Li, Yun; Wang, Chaozi; Walter, M. Todd (Geoderma, 2022)
•Addition of HA significantly increased the total loss of clay from soil.•HA had a significant impact on SP and PP loss in kaolinite mixed soil.•Integrated P transport model simulated well temporal variation of clay, P and TOC.•Competitive adsorption of P and HA led to greater loss of SP and PP in runoff. Phosphorus (P) transport from soil to runoff is affected by the chemical adsorption of P by organic matter, or clay minerals. However, little information is available on the relative effects of different clay minerals on P adsorption in the presence, or absence of humic acid (HA). To achieve this objective, a rainfall erosion experiment was carried out in a cylindrical glass container with a basal area of 45 cm2. The experiment used four soil mixtures, namely kaolinite mixed soil (KMS), montmorillonite mixed soil (MMS), kaolinite mixed soil treated with HA (KMS-HA), and montmorillonite mixed soil treated with HA (MMS-HA), to analyze the influence of HA on soil erosion and loss of P. The experimental results showed that the cumulative loss of clay was highly significantly (p < 0.01) correlated with HA. The total loss of clay from KMS-HA and MMS-HA was five times and 1.7 times that from KMS and MMS, respectively. The results of the experiments showed that the addition of HA had a significant (p < 0.05) impact on the loss of soluble phosphorus (SP), and particulate phosphorus (PP) from the KMS, respectively, but did not significantly influence the SP and PP cumulative loss from the MMS. Temporal variation and inter-relationship of clay, SP, and PP in the soil matrix and runoff, as well as total organic carbon (TOC), were simulated using an integrated P transport model. The values for the coefficient of determination (R2, all greater than 0.73) indicated that the transport model performed well. The results of the experiments and simulations showed that there was competition between P and HA for adsorption onto clay particles, especially for kaolinite, resulting in the release of more SP and PP to runoff. This highlights why more attention needs to be given to HA in nutrient loss management.